Policy Analysis on Tax Amnesty, Tax Compliance, and Tax Audit on Tax Revenue: Bibliometric Analysis - Salma, Aulia Mutiara; Larasati, Ayuning; Melgasari, Diny; Suryanto, Tulus (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2022)
Tax is one of the state revenues used to finance the State Expenditure Budget (APBN). This study aims to provide empirical evidence of the effect of implementing tax amnesty, tax compliance, and tax audit policies on tax revenues. The method used in this research is descriptive quantitative method. Data collection uses the help of the Harzing's Publish or Perish program with the keywords used Tax amnesty, Tax Compliance, Tax audit. From the results of the research carried out, then mapping the findings using the VOSviewers application to be taken as a bibliometric analysis tool to visualize the network of authors and keywords. The results of the study show that tax amnesty, tax compliance, and tax audits have an effect on tax revenues. The tax amnesty policy is more effective in increasing tax revenue compared to tax compliance and tax audits. Keywords: Tax Amnesty, Tax Compliance, Tax Audit, and Tax Revenue